Recovering Ancient and Medieval Contemplative Taxonomies as an Alternative to Bloom’s Taxonomy of Educational Objectives - Steel, Sean (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
Bloom’s taxonomy has become a pedagogical orthodoxy in schools. This paper challenges Bloom’s assumptions about thinking (the cognitive domain) and willing (the affective domain). A careful examination of ancient and medieval understandings – and of Thomas Aquinas’ contemplative taxonomy in particular – demonstrates how Bloom’s taxonomy is both disordered and reductionistic. The thesis of this paper is that, if education is to be truly aimed at our “highest happiness,” we must begin, in some small ways at least, to relate our educational efforts to the pursuit of wisdom. This pursuit, it is argued, involves engaging components of thinking and willing that transcend Bloom’s taxonomy.